T cell mediated hypersensitivity to previously tolerated iodinated contrast media precipitated by introduction of atezolizumab - Munir Pirmohamed; Anna Olsson-Brown; Lorenzo Ressel; Sean Hammond; Joshua Gardner; Serat-E Ali; Paul Thomson; Carol Jolly; Dan Carr; Dean Naisbitt (Journal for ImmunoTherapy of Cancer, 2021)
Many adverse reactions associated with immune checkpoint inhibitor (ICI) treatments are immunologically driven and may necessitate discontinuation of the ICI. Herein, we present a patient who had been administered the radio contrast media amidotrizoate multiple times without issue but who then developed a Stevens-Johnson syndrome reaction after coadministration of atezolizumab. Causality was confirmed by a positive re-challenge with amidotrizoate and laboratory investigations that implicated T cells. Importantly, the introduction of atezolizumab appears to have altered the immunologic response to amidotrizoate in terms of the tolerance–elicitation continuum. Proof of concept studies demonstrated enhancement of recall responses to a surrogate antigen panel following in-vitro (healthy donors) and in-vivo (ICI patients) administrations of ICIs. Our findings highlight the importance of considering all concomitant medications in patients on ICIs who develop immune-mediated adverse reactions. In the event of some immune-related adverse reactions, it may be critical to identify the culprit antigen-forming entity that the ICIs have altered the perception of rather than simply attribute causality to the ICI itself in order to optimize both patient safety and treatment of malignancies.